THE DEVELOPMENT OF LEARNING KITS BASED ON CAUSALITY MODEL TO IMPROVE CREATIVITY THINKING SKILLS MOMENTUM AND IMPULSE OF STUDENTS - Faresta, Rangga Alif; Warodiah, Yudia Nikmatul (PROGRES PENDIDIKAN, 2024)
Teachers still do not fully pay attention to the creative thinking abilities of students. This is seen from the selection of models in the teaching tools used by teachers in teaching. The selection of teaching models that tend to be directed towards direct teaching results in students being less active in following physics learning. Therefore, this research aims to determine the feasibility of a causality model learning device to improve creative thinking skills on the material of momentum and impulse. This type of research includes research and development (R&D), using a 4D model design. However, in this research, only the development stage is carried out. The research procedures carried out refer to the steps of developing the 4D model, namely define, design, and develop. The developed learning device consists of a syllabus, lesson plans, and pre-tasks. Data collection is done through validation of the learning device by validators. The results of the validation of the learning device reached an average validation value of 87.50% with the criteria of very valid and the reliability score is 92.30%. Based on these results, it can be concluded that the causality model learning device to improve the creative thinking skills of momentum and impulse students is suitable to be used in learning.